"Ja, vi tror på Snåsamannen" - Hoff, Siri Jannicke Wasa (Tidsskrift for kulturforskning, 2009)
In 2008, Gyldendal publishing house and the author Ingar Sletten Kolloen presented a biography about an 83-year-old clairvoyant healer called Snåsamannen. After publication, the media became aware of the man with the healing hands, and Snåsamannen was interviewed by various newspapers, and on television and radio stations. The book became a best-seller, and the massive attention in the media shows that folk medicine is a living part of our society. Previously stories about folk medicine have mostly been transmitted orally, and people have talked about their experiences in private. Today, both women and men talk openly to the media, about their encounters with healing and folk medicine , and during the last year many different types of newspapers have written about Snåsamannen.